Transcriptome analyses provide insights into maternal immune changes at several critical phases of giant panda reproduction. (September 2020) - Wu, Wei; Wu, Honglin; He, Ming; Zhang, Liang; Huang, Yan; Geng, Yang; Liu, Jinhua; Wang, Qian; Fan, Zhenxin; Hou, Rong; Yue, Bisong; Zhang, Xiuyue
Abstract: Giant pandas ( Ailuropoda melanoleuca ) possess highly specialized reproductive characteristics, but the maternal immune changes during reproduction are largely unclear. Here, 20 blood transcriptomes were used to determine immune changes at four key phases of giant panda reproduction, and a total of 4640 differential expression genes were identified. During estrus, six immune-related genes ( TLR4, IL1B, SYK, SPI1, CD80, and ITK ) were identified as hub genes. The up-regulation of the TLR family genes ( TLR4, TLR5, TLR6, and TLR8 ) and inflammatory response related genes ( IL1B ) may reflect innate immune enhancement and local tissue remodeling events, while the up-regulation of SYK and SPI1, and the down-regulation of CD80 and ITK suggested that the enhanced humoral immunity and inhibited cellular immunity of female giant pandas during estrus. During early pregnancy, antigen presentation related genes and proinflammatory cytokine ( IL1B ) were down-regulated. This may indicate that partial immune functions were suppressed in early pregnancy to achieve immune tolerance, including reducing inflammatory to protect embryos. By the late pregnancy, the antiviral related genes were up-regulated to strengthen defenses against external pathogen infection. KLRK1, which acts as a primary activation receptor for NK cells, was down regulated in estrus and pregnancy, suggesting that the activities of NK cells were inhibited, and KLRK1 may play a key role in the regulation the activities of pbNK cells during reproduction of giant pandas. Our results showed that there was no significant immune change in lactating females (post-natal 2 months) compared to anestrus females. This is the first time to observe the immune changes of giant panda during the breeding period and our data is expected to provide valuable resources for further studies on reproductive immunology of giant pandas. Highlights: The innate immune and inflammatory response of female pandas may be enhanced during estrus. The maternal immune function of giant panda in early pregnancy is inhibited. In late pregnancy, antiviral related genes were up-regulated.